ACTIVITY DIRECTIONS OF THE STATE DEBT SERVICE GUARANTEE FUND IN PUBLIC DEBT MANAGEMENT - Komolov Odiljon Sayfidinovich; Yusupov Bekzodjon Abdurakhim oglu (American Journals, 2025)
The article highlights the purpose, tasks, and activity directions of the State Debt Service Guarantee Fund, which plays an important role in the public debt management system of the Republic of Uzbekistan. In addition, the study analyzes the growth trends of public debt in Uzbekistan and examines the revenues and expenditures of the State Debt Service Guarantee Fund.
Keywords: Public debt, Guarantee Fund, financial stability, debt policy, external debt, budget deficit, debt management.